Analysis Of Injector Flowing On Auxiliary Engine On KMP. Portlink - Irwan, Irwan; Ilham, Chairul Insani; Novrianti, Novrianti (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
Auxiliary Engine is an engine in which air is compressed to a high enough temperature to ignite diesel fuel injected into the cylinder, where combustion and emission drive pistons which convert the chemical energy in the fuel into mechanical energy. Good fogging is needed in diesel engines, in order to get maximum power. The condition of the injectors on the Auxiliary Engine greatly affects the condition of the Auxiliary Engine itself. The presence of injector damage can affect the operating conditions of the Auxiliary Engine, so the condition of the injectors must always be maintained. The research method that the author uses in the preparation of this thesis is a qualitative research method as a data analysis technique to analyze the problems that exist in the Auxiliary Engine, namely what factors cause injector damage to the Auxiliary Engine, the impact and what efforts are made to overcome these factors. Of these problems by systematically identifying various factors on human factors, environment, methods, machines to formulate strategies to be taken. Based on the results of research that has been done by the author on the ship KMP. PORTLINK, it can be concluded that the damage to the injector on the Auxiliary Engine is caused by two factors, namely the high operational schedule of the ship, and the infrequent maintenance of the Auxiliary Engine injector and the use of inappropriate fuel. To overcome these factors, maintenance can be carried out according to PMS time, as well as good filtering on low-quality fuel. Based on the results of research that has been done by the author on the ship KMP. PORTLINK, it can be concluded that the damage to the injector on the Auxiliary Engine is caused by a clogged nozzle and looseness in the injector component.